Interaction between Migration and Economic Growth through Unemployment in the Context of Political Instability in the MENA Region - Mtiraoui, Abderraouf (International Journal of Economics and Financial Issues, 2024)
This article aims to elucidate the direct and indirect repercussions of migration on economic growth, specifically examining its interaction with unemployment within a backdrop of political instability. Employing a simultaneous equation model, our study spans the period from 1990 to 2020, providing comprehensive insights into the intricate dynamics at play. The findings affirm a global resonance, particularly resonating across the majority of Middle East and North Africa (MENA) nations. Our empirical contribution endeavors to underscore the synergies between political instability and migration while unraveling the nuanced interplay among migration, unemployment, and economic growth within the confines of our study region. This analysis not only contributes to the existing body of knowledge but also underscores the complexity and multifaceted nature of these interactions in the MENA region.